Nudging immunity: the case for vaccinating children in school and day care by default - Giubilini, A; Caviola, L; Maslen, H; al., E (Springer Verlag, 2019)
Many parents are hesitant about, or face motivational barriers to, vaccinating their children. In this paper we propose a type of vaccination policy that could be implemented either in addition to coercive vaccination or as an alternative to it in order to increase paediatric vaccination uptake in a non-coercive way. We propose the use of vaccination nudges that exploit the very same decision biases that often undermine vaccination uptake. In particular, we propose a policy under which children would be vaccinated at school or day-care by default, without requiring parental authorization, but with parents retaining the right to opt their children out of vaccination. We show that such a policy is 1) likely to be effective, at least in cases in which non-vaccination is due to practical obstacles, rather than to strong beliefs about vaccines, 2) ethically acceptable and less controversial than some alternatives, because it is not coercive and affects individual autonomy only in a morally unproblematic way, and 3) likely to receive support from the UK public, on the basis of original empirical research we have conducted on the lay public.